The Sparkle Egg - Hardie, Jill, 1970-; Kornacki, Christine (Nashville, Tennessee : Ideals Children's Books, 2014)
Sam feels guilty after lying to his parents about a spelling test, but they teach him how an empty Easter egg, decorated with jewels, can symbolize accepting Jesus's forgiveness.
Keywords: Honesty -- Fiction; Forgiveness -- Fiction; Easter -- Fiction; Conduct of life -- Fiction; Christian life -- Fiction; Easter stories; Forgiveness -- Juvenile fiction; Easter stories; Forgiveness; Fiction; Juvenile works